Mexico : Financial Sector Assessment Program Update; Technical Note; The Pension Annuity Market. (IMF Staff Country Reports; Country Report ;, 2007)
This paper presents a technical note on Mexico's Financial Sector Assessment Program update. The Mexican experience displays interesting characteristics that provide lessons for other countries that still need to design the decumulation phase of their newly established second pillars. The rationale for the choice of specialized annuity providers has been, on the one hand, to avoid the contagion effect from composite life and nonlife insurance companies operating annuities, and on the other hand, the implicit government guarantee associated with a benefit provision for which participation has been mandated by the federal government.